La adquisición del lenguaje, un resumen en 2011 - López-Ornat, Susana (Revista de Investigación en Logopedia, 2011)
A short synthesis follows, aimed at presenting a global frame for the understanding of the language acquisition process. The state of the art of research on that process is reviewed from an emergentistconstructivist perspective. Present day theoretical alternatives are described, and so is the methodological progress of the language development field along the last two decades, as explained through some examples. Some questions which nowadays guide research in language acquisition are presented, together with the steps that are being taken towards their clarification.